EXPERIMENTAL INVESTIGATION OF STRENGTH STEEL BEAMS REINFORCED HORIZONTALLY DELAY - , Ю. О. (Municipal economy of cities. Series: «Economy science», 2013)
The results of the experimental researches of steel beams reinforced horizontal braces at different levels of preloading are presented in this work.